Effect of Psychosocial Factors in the Use of Telemedicine - Salsabila Salsabila; Ernawaty Ernawaty (Universitas Islam Bandung, 2022)
Telemedicine is the impact of industrial revolution 4.0, which urges the development of health system technology to increase access to health services. This condition is contrary to the use of society, where consumers decide to stop using telemedicine services after several benefits. This study aims to identify the effect of psychosocial factors on consumer decisions in utilizing telemedicine services. This study was analytical observational research with a cross-sectional design. The population of this study was consumers aged 17–40 years who needed access to health services. Data collection was done in January–May 2021 by distributing online questionnaires tested for validity and reliability to 198 respondents in Surabaya. The data obtained were analyzed using logistic regression. The results showed that consumer psychological factors, including motivation, psychology, and learning, influenced decisions to use telemedicine services (p<0.05). Meanwhile, the social factors of the reference group did not have a significant effect (p>0.05). High motivation, positive perception, learning, and family encouragement influence consumer decisions to use telemedicine services, whereas the reference group does not. This research can be used as a consideration for healthcare technology developers and decision-makers in promoting the use of telemedicine so that it continues to be used in the long term.